A comment on amenities and urban and regional development - Hogni Kalso Hansen; Thomas Niedomysl (European Regional Science Association (ERSA), 2010)
Migration of Creativity - A Literature Review of a Growing Field Recent years have generated a growing literature on the location dynamics and migration patterns of talents. The underlying argument is that if regions are capable of attracting and retaining talents they have better odds for being competitive in a knowledge economy that is said to be increasingly dependent upon creative inputs. Contributions to this debate range from an emphasis on the role of amenities to the evolutionary trajectories of regions as explanations for why some regions succeed in attracting creative mindsets while other regions do not. Many of these contributions combine insights from different disciplines. This paper aims to offer a systematic review of the literature within this growing field.
Keywords: 330